Effect of functional appliance therapy on the quality of life in skeletal Class II malocclusion - Imani Mohammad Moslem; Tabaii Elaheh Seyed; Jamshidi Saba; Arab Sepideh (Sciendo, 2018)
A Class II malocclusion is a common orthodontic problem that may affect social acceptance and the self-esteem of the patient. The aim of the present study was to evaluate the effect of functional appliance therapy on the oral health-related quality of life (OHRQOL) of patients presenting with a skeletal Class II malocclusion due to mandibular deficiency.